Health and well-being of older Europeans - Thogersen-Ntoumani, Cecilie (Springer Netherlands, 2014)
The aim of this encyclopedia is to provide a comprehensive reference work on scientific and other scholarly research on the quality of life, including health-related quality of life research or also called patient-reported outcomes research.